Некоторые аспекты реконструкции индоевропейских гуттуральных - Кретов, Алексей Александрович (Baltistica, 1989)
SOME ASPECTS OF THE INDO-EUROPEAN GUTTURALS’ RECONSTRUCTIONThe article concerns the problem of Indo-European gutturals and maintains the hypothesis of one guttural series. It insists on the existence of the correspondence between labio-velars in centum languages and sibilants in satem languages, though an opposite opinion has persisted for about a century. The correspondence was not discovered because: (1) the reconstruction of the gutturals was based primarily on the literary languages, (2) main attention was paid to phonetics. The proper solution of the problem calls for the use of the dialectal data with due regard for semantics. The former (Russian dialects) and the latter are explored in the paper. Some new etymologies are presented.
Keywords: indoeuropiečių